2017
DOI: 10.1063/1.4975113
|View full text |Cite
|
Sign up to set email alerts
|

In-situ synchrotron x-ray characterization of K2CsSb photocathode grown by ternary co-evaporation

Abstract: K2CsSb is a promising photocathode candidate to serve as an electron source in next-generation light sources such as Free Electron Lasers (FEL) and Energy Recovery Linacs (ERL). As the traditional recipe for creation of K2CsSb photocathodes typically results in a rough surface that deteriorates electron beam quality, significant effort has been made to explore novel growth methods for K2CsSb photocathodes. In this paper, a method of ternary co-evaporation of K, Cs, and Sb is described. By using in-situ synchro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 11 publications
2
16
0
Order By: Relevance
“…A different grain structure has been observed based on the acquired diffraction pattern from the codeposited as-grown K-Cs-Sb photocathode which has a predominant (2 2 2) peak and weak (2 2 0) peak, when compared with the powder diffraction pattern acquired from polycrystalline K 2 CsSb samples prepared by traditional recipe which has a predominant (2 2 0) peak [22,23]. Such a result is in good agreement with the previous study on the characterization of codeposited K-Cs-Sb photocathodes [5] and this indicates that a highly textured K-Cs-Sb thin film is formed by the codeposition method which contrasts with the polycrystalline film formed by the sequential deposition.…”
Section: X-ray Diffractionsupporting
confidence: 89%
See 3 more Smart Citations
“…A different grain structure has been observed based on the acquired diffraction pattern from the codeposited as-grown K-Cs-Sb photocathode which has a predominant (2 2 2) peak and weak (2 2 0) peak, when compared with the powder diffraction pattern acquired from polycrystalline K 2 CsSb samples prepared by traditional recipe which has a predominant (2 2 0) peak [22,23]. Such a result is in good agreement with the previous study on the characterization of codeposited K-Cs-Sb photocathodes [5] and this indicates that a highly textured K-Cs-Sb thin film is formed by the codeposition method which contrasts with the polycrystalline film formed by the sequential deposition.…”
Section: X-ray Diffractionsupporting
confidence: 89%
“…The simulation yields a rms roughness of 1.15 nm. The simulated thickness and roughness of the photocathode film grown by the three-element codeposition method are on a comparable level to those reported in a previous study [5]. After the decay is finished, the period of the XRR oscillations appears to be slightly larger, indicating a reduced film thickness.…”
Section: X-ray Diffractionsupporting
confidence: 81%
See 2 more Smart Citations
“…Models suggest that at the envisaged gradients for SRF photoinjectors (15)(16)(17)(18)(19)(20) the surface roughness of the photocathode must be reduced to values of R q ≤ 10 nm to maintain a roughness induced emittance contribution that is below the intrinsic emittance [9,10]. From recent works of Schubert et al and Ding et al it is apparent that the final roughness of alkali antimonide photocathodes depends strongly on the growth procedure and the crystallization processes involved [11,12]. It has been shown that the sequential growth process delivers very rough photocathodes due to the multiple phase transitions, while smoother photocathodes can be grown using new growth procedures such as triple evaporation of Cs-K-Sb using pure alkali metal sources and magnetron sputtering [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%